GAMBARAN KUALITAS HIDUP LANSIA DI PANTI SOSIAL TRESNA WERDHA BUDI LUHUR DAN LANSIA DI KELURAHAN PAAL V -KOTA JAMBI - Mila Triana Sari; Susanti Susanti (Jurnal Ilmiah Universitas Batanghari Jambi, 2017)
Quality of life research focused to the aspects of physical and psychological health. The  research goal were to know the description of the quality of life of elderly in PSTW Budi Luhur and Paal V  Village of Jambi City in 2016. This research design is quantitative descriptive research. The number of samples in the study were 20 subjects each elderly PSTW Budi Luhur and Paal V Village of Jambi city, elected by Proportional Random Sampling. Data collected by using the questionnaire of the WHOQOL. Data analysed as in an univariate and presented in the form of frequencies distribution and narration in tekstuler. The results shown that the quality of life of elderly have the same percentages which as many as 9 (45%) were  good and 11 (55%) were poor quality of life  of elderly in PSTW Budi Luhur has and also in Paal V Village. PSTW Management supposed to enhancer activities of daily living and social and more  religious activities such as personal hygiene and places sircumstance, exercises and religious on a regular basis. The Head of Paal V Village in Jambi City supposed to develop existing community health care of elderly.   Keywords   : Quality of life, Elderly, PSTW Budi Luhur, Neighborhood Paal V